Node Stability Aware Energy Efficient Single Node Failure Recovery Approach for WSANs - Ranga, Virender; Dave, Mayank; Verma, Anil Kumar (Malaysian Journal of Computer Science, 2016)
The inter-actor connectivity is absolutely crucial in wireless sensor and actor networks for timely responses to events generated in the network. Due to the sparse nature of the network, the failure of one or more actor nodes results in network partitioning problem very frequently. To provide effective connectivity between disjoint segments, a self-healing solution is required with a small number of involved actor nodes. Also, their travelling distances should be small. To find stable actor nodes with their small moving distance for recovery is an NP-hard problem for large scale problems. However, the present literature requires broadcasting of route request packets to find the nodes or location for recovery, which consumes more network energy and consequently decreases the network lifetime. In this study, we propose an algorithm called Node Stability aware Connectivity Restoration Algorithm (NSCRA) to tackle such network partitioning problem in an energy efficient way with stable actor nodes. The stability of node(s) is calculated by using controlled packet forwarding probability (i.e. node route request) that is based upon neighbour energy decay rate. The selection of node is based on its backup power to avoid further network partitioning (i.e. overlapped or collocated failures) during recovery. Our proposed approach performs not only energy efficient recovery due to the participation of stable nodes, but also reduces the message overhead of the network. The experimental simulation results show that proposed approach outperforms other existing state-of-the-art approaches.